2017
DOI: 10.1016/j.nrjag.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of groundwater potentiality survey in south Ataqa-northwestern part of Gulf of Suez by using resistivity data and site-selection modeling

Abstract: The integration between advanced techniques for groundwater exploration is necessary to manage and protect the vital resources. Direct current (DC) resistivity geoelectrical technique, Enhanced Thematic Mapper Landsat (ETM+) images and a geographic information system (GIS) are integrated to identify the groundwater potentiality in the study area. The interpretation of the one-dimensional (1-D) inversion of the acquired resistivity data are implemented for mapping the fresh to slightly brackish water aquifer. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Employed remote-sensing and GIS techniques to identify potential areas for groundwater in the Musi-basin by the use of various maps (these include hydro-geomorphological, structural, geological, slope, drainage, land use or land cover and slope. Other investigators that have used remotely-sensed data to carry out groundwater investigations either as stand-alone or as integrated techniquewith other geophysical techniques include Edet et al (1994), Batalan and De Smedt (2000), Valeriano et al (2006), Wright et al(2006, Grohmann et al (2007) and Sultan et al (2017). The use of remotely sensed data in hydrogeological investigation has been able to provide complementary information about the subsurface of an area before borehole can be drilled (Goki et al 2010;Anudu et al 2011;Omeje et al, 2014;Sultan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Employed remote-sensing and GIS techniques to identify potential areas for groundwater in the Musi-basin by the use of various maps (these include hydro-geomorphological, structural, geological, slope, drainage, land use or land cover and slope. Other investigators that have used remotely-sensed data to carry out groundwater investigations either as stand-alone or as integrated techniquewith other geophysical techniques include Edet et al (1994), Batalan and De Smedt (2000), Valeriano et al (2006), Wright et al(2006, Grohmann et al (2007) and Sultan et al (2017). The use of remotely sensed data in hydrogeological investigation has been able to provide complementary information about the subsurface of an area before borehole can be drilled (Goki et al 2010;Anudu et al 2011;Omeje et al, 2014;Sultan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…He observed that most of these faults are normal, and just a small number of them are diagonal, with substantial dip-slip movement and negligible strike-slip components. Sultan et al (2017) classified the major fault trends into NNW-SSE, E-W, and WNW-ESE faults. The bulk of the faults are located in a northwest-southeast direction.…”
Section: Geographical Location and Geology Of The Areamentioning
confidence: 99%
“…In a basement terrain where groundwater accumulation is a function of weathered layer's thickness and fractured bedrock, the layer's thickness is used to classify the vertical extent at which each geological type can be covered in the subsurface. The thickness and depth of the last layer in geoelectrical analysis is infinite (Patra and Nath, 1999;Obiabunmo et al, 2014;Anomohanran et al, 2017;Sultan et al, 2017). In a crystalline terrain, the thicker the overburden, the more viable the groundwater exploration becomes in such environment.…”
Section: Distribution Of Curvesmentioning
confidence: 99%
“…Though its field data is easy to acquire and fast, the major drawback is the shallow depth of investigation due to low signal strength (Loke, 1997;Hago, 2000). Furthermore, Shendi and Elrayes (1992), Yadav et al (1997) 2017, and Sultan et al (2017) have adopted the Geoelectrical technique either as a stand-alone method, or integrated with other geophysical methods to search for groundwater occurrence in the subsurface. Hence, this study is aimed at using Vertical Electrical Sounding (VES) to establish drillable zone(s) for groundwater and recommend the appropriate depth to which boreholes can be sunk in the area to exploit an appreciable volume of water in the subsurface.…”
Section: Introductionmentioning
confidence: 99%